2009
DOI: 10.1017/s0022112008005715
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear processes in two-dimensional mixing layer dynamics and sound radiation

Abstract: In this study, we consider the effects of linear and nonlinear instability waves on the near-field dynamics and aeroacoustics of two-dimensional laminar compressible mixing layers. Through a combination of direct computations, linear and nonlinear stability calculations, we demonstrate the significant role of nonlinear mechanisms in accurately describing the behaviour of instability waves. In turn, these processes have a major impact on sound generation mechanisms such as Mach wave radiation and vortex pairing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 43 publications
7
51
0
Order By: Relevance
“…In the supersonic jets modelled here, the disparity of wavelengths in the two regions is not large (see figure 6, and also figure 8 appearing later), so that PSE is able to approximate both domains. The noise field associated with subsonic shear layers does not satisfy this condition: this explains the corresponding failure of PSE reported by Cheung & Lele (2009). …”
Section: Comparisons Of Near-field Pressurementioning
confidence: 92%
See 1 more Smart Citation
“…In the supersonic jets modelled here, the disparity of wavelengths in the two regions is not large (see figure 6, and also figure 8 appearing later), so that PSE is able to approximate both domains. The noise field associated with subsonic shear layers does not satisfy this condition: this explains the corresponding failure of PSE reported by Cheung & Lele (2009). …”
Section: Comparisons Of Near-field Pressurementioning
confidence: 92%
“…Apart from the issue of intermittency, the consideration of the supersonic jet affords the direct acoustic modelling with PSE in another manner. Cheung & Lele (2009) demonstrated that PSE successfully predicts the acoustic field in a laminar supersonic mixing layer, but fails in a subsonic case: a hybrid PSE-acoustic analogy approach was used to circumvent the latter problem. This behaviour is explicated in our subsequent discussion.…”
Section: Introductionmentioning
confidence: 99%
“…This method therefore does not directly yield the acoustic field, although it can be recovered from an acoustic analogy. 10 Owing to the increasing computing power modal and non-modal studies of fully non-parallel flows have recently become accessible, in particular through the use of matrixfree methods. 7,15,17,22,27 In the present study, a modal stability analysis of axisymmetric perturbations is performed in order to elucidate the physical origin of the preferred mode.…”
Section: Introductionmentioning
confidence: 99%
“…First, at the foundation level is the vectorial velocity equation (20) or (21). Although redundant for the shearing process, it is a good preparation for the compressing process because all dynamic/thermodynamic variables except the squared sound speed are removed therefrom, and the coupling mechanisms with shearing and entropy processes are clearly exhibited.…”
Section: Discussionmentioning
confidence: 99%